Fragment based drug design and diversity-oriented synthesis of carboxylic acid isosteres. Issue 22 (15th November 2020) - Ferri, Martina; Alunno, Manuel; Greco, Francesco Antonio; Mammoli, Andrea; Saluti, Giorgio; Carotti, Andrea; Sardella, Roccaldo; Macchiarulo, Antonio; Camaioni, Emidio; Liscio, Paride
Graphical abstract: Highlights: With Fragment Based Drug Design (FBDD) and Diversity-Oriented Synthetic (DOS) methodologies, a small library of molecular fragments endowed with acidic properties was synthesized. The pKa of each fragment was estimated and experimentally determined. The small library of fragments showed good versatility both in synthetic and physico-chemical properties. Abstract: The medicinal chemist toolbox is plenty of (bio)isosteres when looking for a carboxylic acid replacement. However, systematic assessment of acid surrogates is often time consuming and expensive, while prediction of both physicochemical properties (logP and logD) as well as acidity would be desirable at early discovery stages for a better analog design. Herein in this work, to enable decision making on a project, we have synthesized by employing a Diversity-Oriented Synthetic (DOS) methodology, a small library of molecular fragments endowed with acidic properties. By combining in-silico and experimental methodologies these compounds were chemically characterized and, particularly, with the aim to know their physicochemical properties, the aqueous ionization constants (pKa), partition coefficients logD and logP of each fragment was firstly estimated by using molecular modeling studies and then validated by experimental determinations. A face to face comparison between data and the corresponding carboxylic acid might help medicinal chemists in finding the best replacement to be used. Finally, in the framework of Fragment Based Drug Design (FBDD) the small library of fragments obtained with our approach showed good versatility both in synthetic and physico-chemical properties.